Surveillance Neck Sonography After Thyroidectomy for Papillary Thyroid Carcinoma: Pitfalls in the Diagnosis of Locally Recurrent and Metastatic Disease. (10th April 2017) - Chua, Wynne Yuru; Langer, Jill E.; Jones, Lisa P.
Abstract : A sonographic examination of the neck performed 6 to 12 months after thyroid surgery in patients with differentiated thyroid cancer is strongly recommended by the American Thyroid Association and considered mandatory by the European Thyroid Association for locoregional surveillance. The aim of this article is to review the normal anatomic changes expected after thyroid surgery and the pathologic mimics of thyroid carcinoma recurrence in post‐thyroidectomy patients as they appear on neck sonography. We hope to offer some pearls to increase diagnostic confidence in this setting.